Clinical analysis of 18 cases of intraumbilical vascular thrombosis - Tang, Guoliang; Ye, Yuting; Li, Yinjiao; Xu, Jing; Zhou, Cuixiang; Chen, Yuying; Zhou, Jun (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to assess the clinical characteristics and perinatal outcomes of intraumbilical vascular thrombosis, with the objective of improving diagnostic accuracy and developing better management strategies to enhance perinatal outcomes.MethodsA retrospective analysis was conducted on 18 cases of intraumbilical vascular thrombosis diagnosed at the Obstetrics Department of the First Affiliated Hospital of Southern University of Science and Technology (Shenzhen, China) between January 2017 and December 2022. Data collected included maternal demographics, details of delivery, pregnancy outcomes, and pathological findings from the placenta and umbilical cord.ResultsIntraumbilical vascular thrombosis was difficult to detect during routine prenatal examinations. Only 3 (16.7%) cases were identified through prenatal ultrasound, while the majority were diagnosed either during labor or through postpartum pathological examination. This condition was associated with several adverse perinatal outcomes, including intrauterine fetal death (4 cases, 22.2%), fetal distress, neonatal brain injury, hypoxic-ischemic encephalopathy, and aspiration pneumonia.ConclusionIntraumbilical vascular thrombosis is a rare yet serious condition that increases the risk of fetal and perinatal complications. Early detection remains challenging, highlighting the need for comprehensive assessments involving prenatal ultrasound, fetal heart rate monitoring, amniotic fluid analysis, and infection screening. Prompt intervention, including timely termination of pregnancy when necessary, is critical to minimizing adverse outcomes.